Social representations of mother-to-child transmission of HIV and its prevention in narratives by young Africans from five countries, 1997–2014: Implications for communication. (August 2018) - Winskell, Kate; Kus, Landy; Sabben, Gaëlle; Mbakwem, Benjamin C.; Tiéndrébéogo, Georges; Singleton, Robyn
Abstract: International recommendations related to the prevention of mother-to-child transmission (PMTCT) of HIV have evolved rapidly over time; recommendations have also varied contextually in line with local constraints and national policies. This study examines how young Africans made sense of mother-to-child transmission (MTCT) and PMTCT and related barriers and facilitators between 1997 and 2014 in the context of these complex and changing recommendations. It uses a distinctive data source: 1343 creative narratives submitted to HIV-themed scriptwriting competitions by young people aged 10–24 from 5 African countries (Senegal, Burkina Faso, Nigeria, Kenya, and Swaziland) between 1997 and 2014. The study triangulates between analysis of quantifiable characteristics of the narratives, thematic qualitative analysis, and narrative-based approaches. MTCT occurs in 8% of the narratives (108), while it is prevented in 5% (65). Narratives differ according to whether they depict MTCT or PMTCT (or, rarely, both), evolve over time, and show cross-national thematic variation. In the aggregate, representations shift in line with increased access to testing and antiretroviral medications, with PMTCT narratives becoming more frequent and MTCT narratives becoming more hopeful as diagnosis becomes the gateway to ART access. However, storylines of intergenerational tragedy in which MTCT is depicted as inevitable persist through 2014. Alongside cross-national differences in theme and tone, narratives from higher prevalence Swaziland and Kenya situate MTCT/PMTCT more centrally within descriptions of life with HIV. Findings illustrate the need to improve communication about PMTCT, reframing negative cultural narratives to reflect the full promise of developments of the past decade and a half. Highlights: Longitudinal and cross-national analysis of social representations of MTCT/PMTCT. Uses distinctive data source: young Africans' creative narratives. Identifies representations of MTCT/PMTCT in general youth population in 5 countries. Analyzes data 1997–2014 as PMTCT availability and WHO recommendations evolved. Links findings to communication needs and practices.